POLA KOMUNIKASI POLITIK DALAM MENAMPUNG ASPIRASI MASYARAKAT - Desman Jaya Gulo; Prietsaweny Riris T Simamora; Rahel Sukatendel (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
Political communication among Political Party Factions in the Regional People's Representative Council (DPRD) of Nias Regency occurred in the acceptance of aspirations regarding infrastructure development and obstacles to solving welfare problems. In this study, the faction of Partai Demokrasi Indonesia Perjuangan (PDI-P) in Nias Regency was chosen as the winning party in the 2019 general election. Qualitative or interpretive methods were used in this study. Research subjects: key informants are Deputy Chair I of the DPRD, the main informants are the Chair of the PDI-P Faction, and the supporting informants are community leaders in the Electoral District (Dapil) members of the PDI-P Faction. The findings of this study are, the PDI-P faction is open to accepting the aspirations of the community; people do not understand about policy formulation; and disruption of coordination with Regional Apparatus Organizations (ODP). The conclusion of this study shows that the Communication Pattern of Partai Demokrasi Indonesia Perjuangan (PDIP) Faction occurs in a circular manner. The pattern of circular communication is reflected in the acceptance of people's aspirations to the PDI-P faction regarding development and re-submitting them to the community in the form of policy priorities. Regarding the results of the policy formulation process, not all prioritize aspirations, so that people feel dissatisfied. On the other hand, the coordination between the PDI-P faction and ODP to be involved in formally accepting aspirations is not well established.